Study of factors that help in assessing the outcome of perforative peritonitis - G. B., Chandan; N., Chandrasekhar; N., Satish Babu; B. M., Pavan (International Surgery Journal, 2019)
Background: Perforative peritonitis is one of surgical emergency associated with increased morbidity and mortality. The current study aims to evaluate etiological factors of the disease and to assess the effectiveness of Mannheim peritonitis index (MPI) and sepsis score of Elebute and Stoner to predict the outcome. Methods: This is a prospective hospital based study conducted in our hospital from June 2016 to July 2018 involving a total of 50 patients with perforative peritonitis. Prognostic factors and the validity of scoring systems were analyzed. Results: Male preponderance was seen in the study (90%). Mortality rate was higher in older patients compared to younger. Mortality rate was more in females (40%). Mortality rate was more in patients with ileal perforation (45%). Delay of >72 hours of presentation was associated with a mortality of 79%. Mortality increased exponentially with MPI score more than 26 (28% mortality) and with sepsis score >20 was 76%. Conclusions: Age over 50, longer duration of perforation, presence of shock on day one, extent of peritoneal contamination and associated medical illness adversely affect prognosis. Enteric and duodenal perforations carry a higher mortality. Both MPI and sepsis score accurately predicted mortality and morbidity rates.